Q-Switching and Mode-Locking in Highly Doped Zr2O3–Al2O3–Er2O3 -Doped Fiber Lasers Using Graphene as a Saturable Absorber - Ahmad, Harith; Thambiratnam, Kavintheran; Muhammad, Farah Diana; Zulkifli, Mohd Zamani; Zulkifli, Ahmad Zarif; Paul, Mukul Chandra; Harun, Sulaiman Wadi (Institute of Electrical and Electronics Engineers (IEEE), 2014)
The application of graphene as a saturable absorber (SA) for generating Q-switched and mode-locked pulses in a Zirconia-Erbium-doped fiber (Zr-EDF) laser is explored. Graphene-based SAs have a very wide operational range, which complements the extended operational bandwidth of the Zr-EDF. The Zr-EDF has an erbium concentration of about 4320 ppm, with absorption rates of 22.0 and 58.0 dB/m at 987 and 1550 nm. The system is capable of generating Q-switched pulses with pulsewidths and energies of 4.6 μs and 16.8 nJ, respectively, as well as peak powers of 3.6 mW at a repetition rate of 50.1 kHz. The Zr-EDF laser can also generate mode-locked pulses with pulsewidths, average output powers, pulse energies, and peak powers of 730 fs, 1.6 mW, 23.1 pJ, and 31.6 W, respectively, at a repetition rate of 69.3 MHz. Both the Q-switched and mode-locked output pulses are highly stable, allowing for their application in a multitude of real-world applications.